Produção de enzimas celulolíticas pelos fungos Trichoderma reesei e Myceliophthora thermophila e aplicação na sacarificação do bagaço de cana-de-açucar - Casciatori, Priscila Aparecida [UNESP] (2015)
Cellulases are essential for the hydrolysis of lignocellulosic materials aiming to the production of second generation ethanol. The solid-state fermentation is a process that allows obtaining high concentrations of enzymes which can be applied in this hydrolysis. The purpose of the current work was producing cellulolytic and hemicellulolytic enzymes by employing the fungi Trichoderma reesei and Myceliophthora thermophila by solid-state fermentation in packed-bed bioreactor and apply these enzymes, combined or not, in the saccharification of sugarcane bagasses. Bagasse in natura, bagasse pretreated with ozone and ultrasound irradiation in alkaline medium and bagasse with hydrothermal pretreatment have been employed. The enzymes production was evaluated by CMCase, filter paper activitie (FPU), xylanase and β-glucosidase activities. For the saccharification experiments with extracts from both fungi no-combined, it has been adopted a central-composed response surface design with 5 replications of the central point, having as factors the volume of enzyme extract and the duration of hydrolysis. The results with both extracts indicated as optimal a volume of 7,0 mL and 6 hours of hydrolysis for the bagasses in natura, pretreated with ozone and ultrasound irradiation in alkaline medium and with hydrothermal pretreatment, except the extract of M. themophila that resulted in 5,0 mL and 6,8 hours for the hydrothermal bagasse. The best results of conversion in glucoses with both extracts were obtained with the bagasse pretreated with ozone and ultrasound irradiation in alkaline medium, which have been 34,0 % for M. themophila and 21,2 % for T. reesei. From these results, it has been elaborated a full factorial design for the hydrolysis experiments employing enzymatic cocktails. The factors used were composition (1:1; 1:3; 3:1) and temperature (45, 55, 65 ºC and alternated). The best result was obtained by...